Chapter 1 Hazy-Clear Beginnings or a Purpose Beyond the Legend - Czekalska, Renata (Taylor & Francis, 2025)
Indian traces in Korean Culture examines the enduring cross-cultural discourse between India and Korea over the centuries, emphasizing the transformative power of cultural exchange beyond geographical and temporal constraints. The book analyses how symbols transcend sensory realms and embody spiritual content and suggests that Indian associations in Korean culture reflect a hybridized nature, seamlessly blending cultural elements. The author presents various facets of the cultural exchange between India and Korea, covering Princess Hŏ Hwang-ok's legendary Indian origins shaping Korean identity, Ilyŏn's strategic documentation of Buddhism's transmission, the influence of Indian figures such as Gandhi and Tagore, an exploration of literature from ancient Buddhist verse to modern poets like Kim Yang-shik and Shiva Ryu, and a study of cultural exchange in K-pop. Facilitating a possible alternative to Huntington’s theory of the clash of civilisations, this book provides evidence that the multifaceted encounters between cultures are a historical process that co-shapes civilisational change on a global scale. The first monograph solely dedicated to India-Korea cultural connection from antiquity to the present, this book offers a paradigm shift, inviting readers to explore fresh insights and reshape their understanding of cultural exchanges. It will be of interest to researchers in intercultural communication, Cultural Studies, Cultural History and Asian Studies, in particular Korea and India.